Membaca 'Kebenaran' Nietzsche - Tandyanto, Yulius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Nietzsche’s early work that gives wide exploration of the idea of truth is his unpublished essay entitled Wahrheit und Lüge in Ausermoralischen Sinne (1872). His controversial statement in this essay was “Truths are illusions”, opening many interpretations among scholars in understanding his position on truth. Sarah Kofman argues that it is useless to speak about truth in Nietzsche’s philosophy, for values are neither true nor false. Referring values to truth means forgetting to place oneself “beyond good and evil.” Unlike Kofman, Maudemarie Clark separates sharply Nietzsche’s critique of metaphysics and his denial of truth. Clark argues that Nietzsche rejects metaphysics and eventually overcomes it in his own work, but also that he ultimately affirms the existence of truths and therefore does not undermine his own theory when he claims truth for his own position. Clark’s strategy in defending her theses tries to explain that there is a turning (Kehre) in Nietzsche’s position. This article wants to offer an interpretation that Nietzsche does not make a new theory of truth in WL, but rather examines and constates truths that hold true. With his subtile and metaphoric style, Nietzsche might want to vivify the symbolic and figurative elements in language before the truth or reality that already escapes languages.